QPSNordic - the General Nordic Questionnaire for Psychological and Social Factors at Work - Dallner, Margareta; Lindström, Kari; Knardahl, Stein; Örhede, Elsa (Arbetslivsinstitutet, 2026)
The study consisted of construction and testing of a questionnaire, QPSNordic, which is a common Nordic questionnaire for psychological and social factors in working life. The study was financed by the Nordic Minister Counsellor (Nordiska Ministerrådet) and the Nordic working environment institutes in Denmark, Finland, Norway and Sweden. Three books and one user manual have been published in the Nordic Minister Counsellor's publication series NORD. In addition, user manuals have been released in the language of each involved country. There are reports on the study and the validity check process in each country. The reports contain reviews on the intelligible and the theoretic background to the psychological and social factors which were chosen to be measured by QPSNordic. The relevant work related psychological and social factors are defined, their theoretic background is described and their association with health and well-being is presented.

The basic principles for the selection of factors to QPSNordic were their relevance and importance for work, health and well-being. The multidisciplinary composition of the project group with experts from different specialties affected the choices in both content and methodology. Data bases from earlier Nordic questionnaires made the ground for the selection of questions in the questionnaire. The new QPSNordic consists of multiple-choice questions about following psychological and social factors in work: job requirement and control, predictability and mastery in work, social factors, leadership, organisational culture, interaction between work and private life, centrality of work, commitment to the organisation and work motivation.

The validity check process contained the data collections from four Nordic countries. The first data collection (n=1015) was made to study the factor structure of the questionnaire. Twenty-six scales were created. The second collection (n=995) was made to test the intelligible and predictable validity of the scales. Inner consistence and retest reliability was estimated for each scale. The final version of QPSNordic contains 129 questions whereof 80 make up the 26 scales.

This data description contains datasets from: School, customer service, pharmaceutical company, 995Index, n955.

Purpose:

QPSNordic is designed to use as an instrument for studying psychological, social and organisational working conditions: 1) In organisation development and interventions, 2) in research of association between work and health and 3) in documentation of changes in working conditions.

Undersökningen innebar konstruktion och testning av ett frågeformulär, QPSNordic, som är ett samnordiskt frågeformulär för psykologiska och sociala faktorer i arbetslivet. Undersökningen finansierades av Nordiska Ministerrådet och de nordiska arbetsmiljöinstituten i Danmark, Finland, Norge och Sverige. Tre böcker om arbetet samt en användarmanual har utgivits i Nordiska Ministerrådets publikationsserie NORD. Dessutom har användarmanualer utgivits på resp lands språk. Det finns rapporter om undersökningen och valideringsprocessen i resp land. I rapporterna finns redogörelse för den begreppsliga och teoretiska bakgrunden till de psykologiska och sociala faktorer som valdes för att mätas av QPSNordic. De relevanta arbetsrelaterade psykologiska och sociala faktorerna definieras, deras teoretiska bakgrund beskrivs och deras samband med hälsa och välbefinnande presenteras.

Huvudprincipen för urval av faktorer till QPSNordic var deras relevans och betydelse för arbete, hälsa och välbefinnande. Den multidisciplinära sammansättningen av projektgruppen med experter från olika specialiteter påverkade valen såväl ifråga om innehåll som metodologi. Databaser från tidigare nordiska frågeformulär utgjorde grund för urvalet av frågor i formuläret. Det nya QPSNordic består av flervalsfrågor om följande psykologiska och sociala faktorer i arbetet: arbetskrav och kontroll, predicerbarhet och "mastery" i arbetet, sociala faktorer, ledarskap, organisationskultur, interaktion mellan arbete och privatliv, arbetets centralitet, "commitment" till organisationen och arbetsmotivation.

Valideringsprocessen innefattade två datainsamlingar från fyra nordiska länder. Den första datainsamlingen (n= 1015) gjordes för att studera faktorstrukturen hos formuläret. Tjugosex skalor bildades. Den andra datainsamlingen (n= 995) gjordes för att testa begrepps- och prediktiv validitet hos skalorna. Inre konsistens och retest-reliabilitet beräknades för varje skala. Den slutliga versionen av QPSNordic innehåller 129 frågor varav 80 utgör de 26 skalorna.

Denna databeskrivning innehåller dataset från: Skola, kundtjänst, läkermedelsbolag, 995Index, n955.

Syfte:

QPSNordic är konstruerat för att användas som instrument för att undersöka psykologiska, sociala och organisatoriska arbetsförhållanden: 1) vid organisationsutveckling och interventioner, 2) vid forskning om samband mellan arbete och hälsa och 3) för dokumentation av förändringar i arbetsförhållanden.
QPSNordic - Frågeformulär om psykologiska och sociala faktorer i arbetslivet utprovat i Danmark, Finland, Norge och Sverige
Keywords: HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap